Transition regimes and security sector reforms in Sierra Leone and Liberia - Ato Kwamena Onoma (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Why are some countries more successful at carrying out post-conflict reconstruction programmes than others? Why has Sierra Leone been more successful in the reform of its armed forces than Liberia has after the end of the Mano River Basin wars? This paper argues that the diverging outcomes are explained by the extent to which post-conflict regimes reflected the distribution of power on the ground in the two countries. Sierra Leone's transition regime reflected the distribution of power between forces on the ground and led to a consultative process that resulted in a moderate reform programme. But the earlier input of key local actors made implementation less difficult. In Liberia the transition regime was built on a repudiation of local power realities. This led to a non-consultative process that resulted in a very radical reform programme. But this lack of consultation has severely compromised the implementation of the reforms.
Keywords: F35; H7; N4; O2; 330; security sector reform; institutional reform; peace building; peace transitions; Sierra Leona; Liberia